Determination of Chemicals and its Isotopic Composition in Tigris River, Iraq - Nada, Kamal B.; Khalaf, Husam Saleem; Al-Dulaimy, Zainab Abbas Hassan; Ahmed, Maha Faisl; Hammodi, Azhar Sadiq (Asian Journal of Chemistry, 2018)
Stable isotope (δ18O, δD) values were determined along with the chemical compositions at 10 different locations along the Tigris river between Baghdad-Ammara cities of Iraq. The physico-chemical parameters and isotopic data were measured. The sampling site represents 34 % of total Tigris river in the republic of Iraq. The systematically increased in values of stable isotope as move from the downstream of the river and the most significantly appears at Kut lake. This increase occurs as a result of several factors, viz. (a) evaporation occurs low water level in the river and its tributaries, and (b) return flow water to the river from irrigation water in groundwater systems. The change in ion distribution and in the isotopic values related directly with the outcome from the groundwater and sewage station's water.